1996
DOI: 10.1021/bk-1996-0640.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risk Reduction Through Mechanism-Based Molecular Design of Chemicals

Abstract: Increased understanding of the mechanistic basis of chemical carcinogenesis and the relationship between molecular structure and carcinogenic activity provides opportunities not only for identifying suspect carcinogens but also for designing chemicals with lower carcinogenic potential. One of the chemical classes in which the structural and molecular basis of carcinogenicity is the most clearly understood is the aromatic amines. This paper summarizes the bioactivation mechanisms and structural criteria for aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…The same approach has been used in design of safer chemicals (33) and pollution prevention (34). An expert system (OncoLogic) has been developed to systematize and codify the agency's SAR expertise in predicting carcinogenic potential of chemicals (26).…”
Section: Overview Of Basicmentioning
confidence: 99%
See 1 more Smart Citation
“…The same approach has been used in design of safer chemicals (33) and pollution prevention (34). An expert system (OncoLogic) has been developed to systematize and codify the agency's SAR expertise in predicting carcinogenic potential of chemicals (26).…”
Section: Overview Of Basicmentioning
confidence: 99%
“…The DBPs were first reviewed to identify chemicals with low concern. Judgments of low cancer concern were based on structural similarity to chemicals with negative cancer data, a lack of structural alert for genotoxicity, or presence of structural features suggestive of low cancer risk via the oral route (26,27,33). Once the DBPs of low concern were removed from the list, a literature search was done for the remaining DBPs.…”
Section: Structure-activity Relationships Cancer Prediction For Disinmentioning
confidence: 99%
“…The case study selected for the present analysis is the aromatic amines. These chemicals have considerable environmental and industrial importance, and toxicological data have been reported for a large number of them [Lai et al, 1996;Sugimura, 1997;Vineis and Pirastu, 1997;Skog et al, 1998;Woo and Lai, 2001]. In previous work we have performed QSAR investigations on the activity and the potency of the aromatic amines, for both mutagenic (Salmonella) and carcinogenic (rat and mouse) endpoints [Benigni et al, 2000[Benigni et al, , 2007aFranke et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…Chemicals with two or more fused rings were all mutagenic. The mutagenic potency was found to increase in the order single ring < diphenyl methane < biphenyl < fused rings, suggesting that perhaps multiring systems do provide a longer conjugation path for the stabilization of intermediate metabolites as proposed by Lai et al [11]. The results indicated that mutagenic activity was influenced by different molecular characteristics in different subclasses of aromatic amines.…”
Section: Qsars For Predicting Mutagenicity and Carcinogenicitymentioning
confidence: 64%